The Effect of Self Efficacy and Emotional Intelligence on Employee Performance through Work Engagement - M. Jelvin Andrea Alza; Slamet Widodo (Management Analysis Journal, 2025)
The Indonesian banking industry is characterized by intense competition, requiring every bank to optimize employee performance to maintain customer trust, reputation, and long-term sustainability. Previous studies have highlighted the role of psychological factors in enhancing employee outcomes, yet the interplay between emotional intelligence, self-efficacy, and work engagement in shaping performance remains underexplored, particularly in regional banks. This study addresses this research gap by examining the effects of emotional intelligence and self-efficacy on employee performance at PT Bank Bengkulu, with work engagement as a mediating variable. This research employed a quantitative, explanatory approach. The population comprised 864 employees across PT Bank Bengkulu’s branch network, from which 274 employees were selected using cluster random sampling. Data were gathered through structured questionnaires and analyzed using the covariance-based structural equation modeling (CB-SEM) approach. The outer model evaluated construct validity and reliability, while the inner model tested hypotheses regarding direct and indirect effects. The findings revealed that both emotional intelligence and self-efficacy positively and significantly affect employee performance, and each also directly enhances work engagement. However, work engagement itself showed no significant impact on performance, nor did it mediate the relationships between the two psychological factors and performance. The results imply that internal psychological strengths particularly emotional intelligence and self-efficacyserve as direct drivers of employee effectiveness, independent of engagement.